Implementasi Single Minute Exchange of Dies (SMED) Saat Pergantian Mold Pada Proses Produksi di PT. IMC Tekno Indonesia - Wibowo, Priyo; Pramudika, Bella (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The basic idea behind lean manufacturing is eliminating waste, which is something that does not add value to the product. In the plastics industry, the application of lean manufacture can maximize production results by reducing the waste that occurs. Lean manufacturing is a method that has a focus on eliminating non-value-added activities or known as waste. One of the waste that occurs in the plastic injection industry is the length of time for changing the mold. In addition to the lean manufacturing method in reducing mold replacement time, there is also the Single Minutes Exchange of Dies (SMED) method. The results showed that applying this method reduced the time for changing the mold by 42.6%